XARAJATLAR HISOBINI RIVOJLANTIRISHDA FRANSUS OLIMLARI HISSASI - Xudaynazarova Dilnoza; Ismoilov Xurshid (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the contribution of French scholars to the development of cost accounting and the formation of modern approaches to cost management. The study analyzes the historical development of accounting and cost accounting in France, highlighting the key stages of its evolution and the main theoretical ideas proposed by French economic thinkers. Particular attention is given to the development of methods for calculating, analyzing, and controlling production costs. The article also explores the influence of the French school of economic thought on modern management accounting and cost analysis systems. The findings indicate that French scholars played an important role in shaping systematic approaches to cost control, improving economic efficiency, and supporting managerial decision-making in enterprises.